Plant density of seed propagated artichoke (Cynara scolymus L.) - Miguel, Alfredo; Baixauli, Carlos; Aguilar, José M.; Giner, Alfonso; Maroto Borrego, José V.; López-Galarza, Salvador; Alagarda, J. (2017)
Using the earlier seed propagated cultivars treated with gibberellic acid (GA), it is possible to follow a similar (but slightly delayed) cycle of the most frequently used cultivar in Spain, the asexually propagated ‘Blanca de Tudela’. However, the vegetative growth of the treated plants is lower. For this reason it may be possible to increase the plant density to obtain higher yields. The experiments, conducted in the 1999-2000 and 2000-2001 seasons, compared combinations of three plant densities (10000, 7500 and 5000 plants ha-1) and GA treatments (three fortnightly sprays at 30 ppm from 7 weeks after planting). The cultivars tested were ‘A-106’ (first season) and ‘Lorca’ and ‘Nun 98465’ (second season). In general, with the early cultivars (‘A-106’ and ‘Lorca’) and GA treatments, the highest plant density produced significantly higher early yields than the lowest plant density. The final yield was not affected by plant density or GA treatments. In the first season plant density did not affect head weight in the GA treated plants, but in the untreated ones the lowest head weight was produced at the highest plant density. In the second season GA treatments did not affect head weight and this was significantly lower than the highest plant density. With the late cultivar (‘Nun 98465’), neither GA treatments nor plant density significantly affected yields or head weight. At the lower plant density, plants covered the entire soil surface producing similar yields.